Anxiety and depression in end-stage COPD - Hill, Kylie; Geist, R.; Goldstein, R.; Lacasse, Y. (European Respiratory Society, 2008)
Although feelings of anxiety and depression are common in patients with chronic obstructive pulmonary disease (COPD), estimates of their prevalence vary considerably. This probably reflects the variety of scales and methods used to measure such symptoms. Regardless of whether anxiety and depression are considered separately or as a single construct, their impact on COPD patients is important. A heightened experience of dyspnoea is likely to be a contributing factor to anxiety. Feelings of depression may be precipitated by the loss and grief associated with the disability of COPD. Smoking has been associated with nicotine addiction, and the factors that contribute to smoking may also predispose to anxiety and depressive disorders. Randomised controlled trials indicate that exercise training and carefully selected pharmacological therapy are often effective in ameliorating anxiety and depression. Most medical illnesses are influenced by the psychological responses and coping mechanisms that patients use. However, anxiety and depression are associated with dyspnoea, fatigue and altered sleep, all of which also occur in COPD. An understanding of the psychological history and coping mechanisms of patients and the role of anxiety and depressive reactions to illness may enable clinicians to reduce these symptoms and improve quality of life among patients with chronic obstructive pulmonary disease. Copyright©ERS Journals Ltd 2008.